Identifikasi Bidang Gelincir Longsor Berdasarkan Metode Electrical Resistivity Tomography (ERT) di Desa Tolango, Kabupaten Gorontalo Utara - Tya Ivanka Hiola; Ahmad Zainuri; Ronal Hutagalung (Universitas Negeri Gorontalo, 2025)
This study aims to analyze the geological conditions and landslide potential in Tolango Village, Anggrek District, North Gorontalo Regency. The research area is predominantly composed of two main lithological units: andesite and alluvial deposits. Field observations, petrographic analysis, and structural measurements were carried out to determine the geological characteristics. In addition, geoelectrical surveys using the Electrical Resistivity Tomography (ERT) method were conducted to interpret subsurface conditions. The results show that the upper layer (1.25–3.75 m) consists of clayey soil with low resistivity values (8.10–100 Ωm), while the lower layer (up to 15.9 m) is composed of andesite bedrock with higher resistivity values (101–7,600 Ωm). A potential slip surface was identified at the contact between these two layers, which becomes critical when water infiltration increases during the rainy season. Structural features such as thrust faults and joints were also observed, indicating tectonic influence on slope instability. Overall, the integration of geological and geophysical data confirms that the area is highly susceptible to landslides, particularly on steep slopes with impermeable clay-rich layers overlying resistant bedrock.